Optimizing Village Fund Management through Local Government Authority: Optimasi Pengelolaan Dana Desa Melalui Otoritas Pemerintah Daerah - Ashar, Bramo Al; Rosnawati, Emy (Indonesian Journal of Public Policy Review, 2025)
General Background: Village funds are a vital instrument for promoting equitable rural development and improving community welfare across Indonesia. Specific Background: The implementation of village fund management requires accountability, transparency, and participation from all community elements to ensure effective governance at the village level. Knowledge Gap: However, limited understanding of how local authorities exercise their power in managing and optimizing these funds remains a challenge. Aims: This study aims to analyze the authority of village governments in managing village funds, focusing on financial planning, allocation, implementation, and accountability mechanisms. Results: The findings reveal that village governments are authorized to use up to 3% of funds for operational needs, with the remaining resources allocated toward infrastructure development and community empowerment programs such as UMKM initiatives. Effective management was strongly supported by participatory planning through Musrenbangdes and oversight by the Village Consultative Body (BPD). Novelty: This study highlights the interconnection between local authority and fiscal decentralization as a framework for sustainable village development. Implications: Strengthening governance capacity and public participation ensures transparency and enhances local economic resilience. Highlights: Village authority plays a crucial role in transparent fund management. Participatory planning ensures community-based development. Fiscal decentralization supports sustainable village growth. Keywords: Village Fund, Local Governance, Accountability, Rural Development, Public Policy